Highly selective catalytic hydrogenation of arenes using rhodium nanoparticles supported on multiwalled carbon nanotubes - Kakade, Bhalchandra A.; Sahoo, Suman; Halligudi, Shivappa B.; Pillai, Vijayamohanan K. (Journal of Physical Chemistry C, 2008)
Rhodium nanoparticles (RhNPs; 4.9 +/- 0.4 nm) supported on multiwalled carbon nanotubes (Rh/MWNT), prepared by simple microwave treatment, show a remarkable catalytic activity for arene hydrogenation with enhanced turnover numbers of similar to 10000; disubstituted arenes show selective conversion of thermodynamically less favorable cis products (>80%). A series of arenes have been tested using various Rh-based catalysts, and a comparison of the results with that of reported rhodium catalysts shows unique selectivity under mild conditions.

High-purity synthesis of scrolled mats of multi-walled carbon nanotubes using temperature modulation - Kakade, Bhalchandra A.; Allouche, Hatem; Mahima, Subhramanyam; Sathe, Bhaskar R.; Pillai, Vijayamohanan K. (Carbon, 2008)
Felt-like mats (6-7 mu m thick) of multimalled carbon nanotubes wrapped into scrolls have been synthesized by chemical vapor deposition from a toluene-ferrocene mixture using a temperature ramp from 680 degrees C to 550 degrees C in hydrogen-argon atmosphere. Thermogravimetric analysis reveals a very low catalyst content of ca. 1.25 wt% in the as-synthesized sample while, X-ray photo electron and Raman spectroscopies suggest the results matching with that of multiwalled carbon nanotubes. Considering, different time scales of various reactions and the diffusion of different reactants and products a tentative base growth mechanism has been proposed as per the available characterization data in conjunction with possible scrolling effects. Thermal expansion effects could explain a tentative mechanism for rolling action of sheets. Interestingly, electrical conductivity measurements as a function of temperature suggest a semiconducting behavior, despite being governed by different electron transport mechanisms with activation energies of 0.33 and 1.03 meV corresponding to two temperature ranges respectively. Cyclic voltammetry and electrochemical impedance analysis show a reversible redox behavior due to very low catalyst content and an irreversible etching of the Fe catalyst after acid treatment. (C) 2007 Elsevier Ltd. All rights reserved.

High aspect ratio nanoscale multifunctional materials derived from hollow carbon nanofiber by polymer insertion and metal decoration - Balan, Beena K.; Kale, Vinayak S.; Aher, Pradnya P.; Shelke, Manjusha V.; Pillai, Vijayamohanan K.; Kurungot, Sreekumar (Chemical Communications, 2010)
A novel high aspect ratio material which can simultaneously display multiple functions such as proton and electron conductivity and electrocatalytic activity has been developed by incorporating both platinum nanoparticles and phosphoric acid doped polybenzimidazole along the inner and outer surfaces of a hollow carbon nanofiber.

High current density, low threshold field emission from functionalized carbon nanotube bucky paper - Kakade, Bhalchandra A.; Pillai, Vijayamohanan K.; Late, Dattatray J.; Chavan, Padmakar G.; Sheini, Farid J.; More, Mahendra A.; Joag, Dilip S. (Applied Physics Letters, 2010)
Field emission studies of bucky paper of multiwalled carbon nanotubes (MWNTs), prepared after microwave (MW) assisted acid functionalization are reported along with a comparison with that of ``as-grown'' sample. MW treated bucky papers reveal an interesting linear field emission behavior in Fowler-Nordheim plot. The field emission currents at preset value are found to be remarkably stable over a period of more than 3 h sustaining current densities of 4.9 mA/cm(2) and 8.5 mA/cm(2) for ``as-grown'' and functionalized sample, respectively. The enhancement in the field emission due to functionalization has been discussed in terms of tip opening and defect induced charge transport caused by intershell and intertubular interaction. (C) 2010 American Institute of Physics. [doi:10.1063/1.3479049]
Keywords: Carbon nanotubes; current density; field emission; fullerenes

High pt utilization electrodes for polymer electrolyte membrane fuel cells by dispersing pt particles formed by a preprecipitation method on carbon ``polished'' with polypyrrole - Unni, SreeKuttan M.; Dhavale, Vishal M.; Pillai, Vijayamohanan K.; Kurungot, Sreekumar (Journal of Physical Chemistry C, 2010)
Pt utilization on carbon black (CB) has been significantly improved by initially utilizing polypyrrole (PPy) as a moiety to ``polish'' the carbon surface and subsequently by dispersing Pt particles formed by a preprecipitation process to minimize their migration into the geometrically restricted areas of the carbon surface. This process strategy has helped to significantly extend the triple-phase boundary as a greater number of Pt particles comes in direct contact with Nafion, leading to a substantial improvement in the overall catalyst utilization. Preliminary analyses such as IR, thermogravimetric analysis, and N(2) sorption confirmed the presence of PPy on the surface. Approximately 50% reduction in the surface area of CB after the controlled in situ polymerization of pyrrole monomer on the carbon surface indicated preferential filling and coverage of pores and other geometrically restricted pockets of carbon surface. On the other hand, by converting Pt into colloids in the preprecipitation method prior to their reduction, the platinum particles are forced to stay on the hybrid support; a major part of which otherwise would have been migrated into the surface pores and defect sites. Platinum particle size on these hybrid supports is 2 times higher than the catalyst prepared by polyol process. However, the electroactive surface area and mass activity are 2 times higher than that of the Pt particles prepared by polyol on hybrid material and are also significantly higher than that of the conventional electrocatalysts prepared by the polyol method. At 0.8 V, the kinetic current density (j(k)) of Pt/C-PPy-Pre obtained from the Koutecky-Levich plot is 1.5 and 2.5 times higher than that of catalysts prepared by the polyol method on PPy-coated carbon and Vulcan XC-72 carbon, respectively. Almost 210 and 160 mW cm(-2) improvement for the maximum power density, respectively with oxygen and air, was obtained with the modified system in comparison to the conventional system when the single cell evaluations were carried out at 60 degrees C with a Pt loading of 0.5 mg cm(-2) in the anode and cathode sides. This enhancement in the cell performance under the two different oxygen partial pressure conditions clearly emphasizes the improved oxygen reduction reaction (ORR) and mass-transfer characteristics of the hybrid electrode material compared to the other catalysts.

Hydrous RuO2-carbon nanofiber electrodes with high mass and electrode-specific capacitance for efficient energy storage - Vellacheri, Ranjith; Pillai, Vijayamohanan K.; Kurungot, Sreekumar (Nanoscale, 2012)
We demonstrate a new strategy for the fabrication of supercapacitor electrodes possessing high mass and area-specific capacitance for efficient charge storage, which can be extremely useful for the development of light, compact and high performance supercapacitors for a variety of high power demanding applications. High mass and electrode area specific capacitances were attained by using Hydrous Ruthenium Oxide (HRO)-Carbon Nanofiber (CNF) hybrid electrodes prepared by the deposition of HRO (similar to 31% Ru content) on both the outer and inner surfaces of a cylindrical hollow CNF having open tips. Electrochemical studies of the uniformly deposited HRO nanoparticles on the CNF surface showed a mass specific capacitance of 645 F g(-1) and an electrode specific capacitance of 1.29 F cm(-2) with a HRO-CNF material loading of 2 mg cm(-2) in the supercapacitor electrodes. The mass specific capacitance of pure HRO is 301 F g(-1), whereas the mass specific capacitance of HRO in the HRO-CNF electrode is similar to 1300 F g(-1), which is very close to the theoretical capacitance of HRO. This enhanced charge storage ability, high rate capability, better cyclic stability and low ESR of the HRO-CNF will be useful for the development of high performance supercapacitors.

Hysteresis and charge trapping in graphene quantum dots - Kalita, Hemen; Harikrishnan, V; Shinde, Dhanraj B.; Pillai, Vijayamohanan K.; Aslam, Mohammed (Applied Physics Letters, 2013)
We report current hysteresis in response to applied voltage in graphene quantum dots of average diameter 4.5 +/- 0.55 nm, synthesized electrochemically using multiwalled carbon nanotubes. In response to step voltages, transient current decay, characteristic of deep and shallow level charge traps with time constants 186 ms and 6 s, is observed. Discharging current transients indicate charge storage of the order of 100 mu C. Trap states are believed to arise due to the fast physisorption of external adsorbates, which are found to have a significant effect on charge transport and changes the resistance of the prepared device by an order of 3. (C) 2013 American Institute of Physics.